Cells of Renin Lineage Are Progenitors of Podocytes and Parietal Epithelial Cells in Experimental Glomerular Disease - Pippin, Jeffrey W. (American Society for Investigative Pathology, 2013)
Glomerular injury leads to podocyte loss, a process directly underlying progressive glomerular scarring and decline of kidney function. The inherent repair process is limited by the inability of podocytes to regenerate. Cells of renin lineage residing alongside glomerular capillaries are reported to have progenitor capacity. We investigated whether cells of renin lineage can repopulate the glomerulus after podocyte injury and serve as glomerular epithelial cell progenitors. Kidney cells expressing renin were genetically fate-mapped in adult Ren1cCreER×Rs-tdTomato-R, Ren1cCre×Rs-ZsGreen-R, and Ren1dCre×Z/EG reporter mice. Podocyte depletion was induced in all three cell-specific reporter mice by cytotoxic anti-podocyte antibodies. After a decrease in podocyte number, a significant increase in the number of labeled cells of renin lineage was observed in glomeruli in a focal distribution along Bowman's capsule, within the glomerular tuft, or in both locations. A subset of cells lining Bowman's capsule activated expression of the glomerular parietal epithelial cell markers paired box protein PAX2 and claudin-1. A subset of labeled cells within the glomerular tuft expressed the podocyte markers Wilms tumor protein 1, nephrin, podocin, and synaptopodin. Neither renin mRNA nor renin protein was detected de novo in diseased glomeruli. These findings provide initial evidence that cells of renin lineage may enhance glomerular regeneration by serving as progenitors for glomerular epithelial cells in glomerular disease characterized by podocyte depletion.